Enhancing crack self-healing properties of low-carbon LC3 cement using microbial induced calcite precipitation technique - Wei, Wenzhu; He, Qinglong; Pang, Sen; Ji, Shengjie; Cheng, Yiluo; Sun, Ninghui; Liang, Yinghao (Frontiers in Materials, 2024)
Limestone Calcined Clay Cement (LC3) is a promising low-carbon alternative to traditional cement, but its reduced clinker content limits its self-healing ability for microcracks, affecting durability. This study explores the application of Microbial Induced Calcite Precipitation (MICP) technique to enhance the crack self-healing capacity of LC3-based materials. Bacillus pasteurii was utilized to induce calcium carbonate precipitation to improve the crack self-healing capacity of LC3, thereby addressing its limited durability due to reduced clinker content. Experimental tests focused on optimizing the growth conditions for B. pasteurii, evaluating the compressive strength, capillary water absorption, and crack self-healing rates of the modified LC3 material. Results showed that under optimal conditions (pH of 9, inoculation volume of 10%, incubation temperature of 30°C, and shaking speed of 150 rpm), the bacterial strain exhibited maximum metabolic activity. The Microbe-LC3 mortar demonstrated a self-healing rate of up to 97% for cracks narrower than 100 μm, significantly higher than unmodified LC3. Additionally, the compressive strength of Microbe-LC3 was enhanced by approximately 15% compared to standard LC3 mortar after 28 days. The capillary water absorption was reduced, indicating improved durability due to the microbial-induced calcium carbonate filling the pores. This study confirms that MICP technology is a viable approach to significantly enhance the performance of LC3, contributing to the development of more durable and sustainable cementitious materials for construction applications.